Actual heat losses in hot water installations in selected medical facilities - Bocian, Martyna (Instal, 2022)
The share of energy consumption in domestic hot water systems in the total energy consumption of buildings is still increasing. The amount of detailed field research on hot water systems is limited compared to heating and cooling systems. The article indicates the problem of excessive heat losses in the circulation lines of domestic hot water installations in the building of the hospital and specialist clinic powered by the heating network. The article presents the results of calculations of the power of hot water exchangers, percentage of heat losses in circulation pipes, and an analysis of the heat demand for domestic hot water over the course of a day, month, year and per building area and the number of patients. The heat loss resulting from the circulation of hot water in the hospital for the entire summer period was 50.54%, while in the clinic it was 79.04%. The largest share of circulation losses in hospitals was recorded on Saturdays (65.04%), and in the clinic – on Sundays (90.40%). Based on the calculations performed, it can be concluded that heat losses resulting from the need to maintain hot water parameters are relatively high. They depend largely on the amount of water consumed and the nature of the building.